The demands of the game - A descriptive analysis of the locomotor demands of Junior International Rugby Union - Flanagan, E.; O`Doherty, P.; Piscione, J.; Lacome, M. (Journal of Australian Strength and Conditioning, 2017)
This study investigated the locomotor demands of junior international Rugby Union. Analysis of running performance was conducted via a Global Positioning System (10 Hz Viper 2TM, Statsports Technologies™, Newry, Northern Ireland, UK) across 2 teams and 10 matches (42 players, 96 match observations) at the 2015 World Rugby Under-20 Championship. Running performance was compared across positional groups over the entire duration of the game and for the peak 5-min maximal intensity period. Both individualized and absolute thresholds were used to assess high-speed running. A cluster analysis was performed both on mean and maximal intensity period data to categorise players into groups with similar running demands. Overall, typical mean running volumes ranged from 3944 to 6209m with the mean relative distance ranging from 56 to 71 m.min-1. During the 5-min maximal intensity period, mean relative distance ranged from 77 to 100 m.min-1 with 16.6-31.9% of the distance covered at a high metabolic load. The results of this study highlight the need to prepare players for elite junior rugby union based on the demands of maximal intensity periods rather than the average game demands. This research study also highlights the importance of physically preparing players in specific positional clusters as the demands of the game differ between them. The recommended positional clusters are: hooker grouped with second row; centre grouped with back three; back row grouped with outhalf and prop and scrum half as two independent groups.